2010
DOI: 10.1186/1749-8090-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Flexible bronchoscopic management of benign tracheal stenosis: long term follow-up of 115 patients

Abstract: BackgroundManagement of benign tracheal stenosis (BTS) varies with the type and extent of the disease and influenced by the patient's age and general health status, hence we sought to investigate the long-term outcome of patients with BTS that underwent minimally invasive bronchoscopic treatment.MethodsPatients with symptomatic BTS were treated with flexible bronchoscopy therapeutic modalities that included the following: balloon dilatation, laser photo-resection, self-expanding metal stent placement, and High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 16 publications
0
44
0
6
Order By: Relevance
“…Therapeutic bronchoscopic modalities include balloon dilatation, laser, APC, electrocauterization, cryotherapy, stent placement, endobronchial chemotherapy and brachiotherapy [28][29][30][31]. When therapeutic bronchoscopy is compared with surgical therapy it is more comfortable and less risky for the patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic bronchoscopic modalities include balloon dilatation, laser, APC, electrocauterization, cryotherapy, stent placement, endobronchial chemotherapy and brachiotherapy [28][29][30][31]. When therapeutic bronchoscopy is compared with surgical therapy it is more comfortable and less risky for the patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…The balloon dilates the stenotic trachea or bronchus by stretching and expanding the bronchial wall, making balloon dilation appropriate for the treatment of cicatric annular strictures. Balloon dilation has been extended to the treatment of tracheobronchial stenoses due to, for example, post-intubation tracheal stenosis, postoperative anastomotic stenosis, granulomatous steno-sis (tuberculosis, histoplasmosis), radiation therapy, mediastinal fibrosis, congenital stenosis, bronchial trauma and bronchial artery embolization [2][3][4][5] . Before balloon dilation, the site, severity, proximal and distal extent, and characteristics of the stricture should be evaluated by conventional radiography, computed tomography scans including threedimensional reconstructions, and/or bronchoscopy.…”
Section: Tracheobronchial Balloon Dilationmentioning
confidence: 99%
“…A review of several representative studies, each including 21-59 patients [2,3,[5][6][7] , found that the technical success rate was 100% and that all patients achieved initial symptomatic improvement. In some of these studies, however, up to 80% of patients required adjuvant treatment, including stent placement and laser therapy [2,3,[5][6][7] .…”
Section: Tracheobronchial Balloon Dilationmentioning
confidence: 99%
See 2 more Smart Citations